2017
DOI: 10.1002/cssc.201701663
|View full text |Cite
|
Sign up to set email alerts
|

Solar Water Splitting Utilizing a SiC Photocathode, a BiVO4 Photoanode, and a Perovskite Solar Cell

Abstract: We have successfully demonstrated solar water splitting using an ewly fabricated photoelectrochemical system with aP tloaded SiC photocathode, aC oO x -loaded BiVO 4 photoanode, and ap erovskite solar cell. Detection of the evolvedH 2 and O 2 with a1 00 %F aradaic efficiencyi ndicates that the observed photocurrent was used for water splitting.T he solar-to-hydrogen (STH) efficiency was 0.55 %under no additional bias conditions.Photoelectrochemical water splitting is an attractive reaction to convert solar ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…After 28 h continuous PEC‐WS operation, the hybrid tandem device showed good robustness, and 94 % of the initial bias‐free photocurrent density was retained (4.3 mA cm −2 ). Referring to the state‐of‐the‐art oxide‐based PEC‐WS devices in the literature, this is an outstanding bias‐free photocurrent density, outperforming similar tandem device approaches, which usually operate at current densities below 1 mA cm −2 (for 1 sun illumination intensity) and use noble‐metal catalysts . Table S2 (Supporting Information) summarizes recent studies on hybrid tandem devices for unassisted water splitting.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…After 28 h continuous PEC‐WS operation, the hybrid tandem device showed good robustness, and 94 % of the initial bias‐free photocurrent density was retained (4.3 mA cm −2 ). Referring to the state‐of‐the‐art oxide‐based PEC‐WS devices in the literature, this is an outstanding bias‐free photocurrent density, outperforming similar tandem device approaches, which usually operate at current densities below 1 mA cm −2 (for 1 sun illumination intensity) and use noble‐metal catalysts . Table S2 (Supporting Information) summarizes recent studies on hybrid tandem devices for unassisted water splitting.…”
Section: Resultsmentioning
confidence: 97%
“…Referring to the state-of-the-arto xide-based PEC-WS devices in the literature, this is an outstanding bias-free photocurrent density, outperforming similar tandem device approaches, which usually operate at current densities below 1mAcm À2 (for 1sun illuminationi ntensity) and use noble-metal catalysts. [7][8][9][22][23][24][25][26][27][28][29] Ta ble S2 (Supporting Information) summarizesr ecent studies on hybrid tandem devices for unassisted water splitting. A long-term stabilityt est confirmed that the Ni foil/Nif oam catalyst structure, as well as the hematite nanowires tructures, ensured excellent protectiono ft he photocathode andp hotoanode in harsh basic solutions (1 m NaOH), respectively.…”
Section: Operation Stability Of Hybrid Tandem Devicementioning
confidence: 99%
“…Analogous to the multi-junction tandem solar cell, perovskite can behave as an ideal wide bandgap top absorber in PV/PEC tandem device. So far, perovskite PVs have been paired with some of the widely studied photoelectrodes made of materials like hematite [167], BiVO 4 [169][170][171][172][173], and Cu 2 O [174] for solar water splitting in PV/PEC configuration. The highest unbiased photocurrent density of ~5.7 mA/cm 2 corresponding to STH efficiency of 6.3% has been realized when used in tandem with BiVO 4 photoanode [169,170].…”
Section: Photovoltaic/thermoelectric Generator (Pv/ Teg) Tandem Devicesmentioning
confidence: 99%
“…[15] Ternary metal oxide systems such as Zn 2 SnO 4 , Mn 2 SnO 4 , BaSnO 3 , and BiVO 4 possess excellent electrical transport properties compared with binary oxide systems. [16][17][18][19] The ternary metal oxides possess higher carrier concentration and higher mobility, which can promote the charge transfer process more effectively. Recently, ternary bismuth vanadate (BVO) material has been explored for potential applications due to its easily tunable electrical and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Many articles are available in the literature which describes for the BiVO 4 on dye degradation and water splitting applications. [18,19] BiVO 4 is widespread for water splitting and photocatalysis applications because of its low bandgap and the possibility to promote electron injection into other semiconductors. [25][26][27] To the best of our knowledge, investigation of the BiVO4 thin film layer as an ETL has not been performed so far.…”
Section: Introductionmentioning
confidence: 99%